Combination of MiR-378 and MiR-210 Serum Levels Enables Sensitive Detection of Renal Cell Carcinoma - Fedorko, Michal; Stanik, Michal; Iliev, Robert; Redova-Lojova, Martina; Machackova, Tana; Svoboda, Marek; Pacik, Dalibor; Dolezel, Jan; Slaby, Ondrej (International journal of molecular sciences, 2015)
Serum microRNAs are emerging as a clinically useful tool for early and non-invasive detection of various cancer types including renal cell carcinoma (RCC). Based on our previous results, we performed the study to analyze circulating serum miR-378 and miR-210 in patients with various histological subtypes of RCC. RNA was purified from blood serum samples of 195 RCC patients and 100 healthy controls. The levels of miR-378 and miR-210 in serum were determined absolutely using quantitative real-time PCR. Pre- and postoperative levels of both microRNAs were compared in 20 RCC patients. Significantly increased serum levels of both miR-378 and miR-210 enabled to clearly distinguish RCC patients and healthy controls with 80% sensitivity and 78% specificity if analyzed in combination (p<0.0001), and their levels significantly decreased in the time period of three months after radical nephrectomy (p<0.0001). Increased level of miR-378 positively correlates with disease-free survival (p=0.036) and clinical stage (p=0.0476). The analysis of serum miR-378 and miR-210 proved their potential to serve as powerful non-invasive diagnostic and prognostic biomarkers in RCC.
Keywords: regulace genové exprese u nádorů; nádory ledvin; nádorové biomarkery; mikro RNA; studie případů a kontrol; Biomarkers, Tumor; Humans; Carcinoma, Renal Cell; lidé středního věku; Kidney Neoplasms; Middle Aged; karcinom z renálních buněk; biomarker; mužské pohlaví; microRNA; Gene Expression Regulation, Neoplastic; ženské pohlaví; blood serum; MicroRNAs; lidé; Case-Control Studies; renal cell carcinoma; Male; Female